PEMBERDAYAAN DAN PENGELOLAAN MAJLIS TAKLIM DI DESA KUNTI, KECAMATAN ANDONG, KABUPATEN BOYOLALI - Fatchurrahman, M; Mujahid, Kasori; Al Java, Abyanudin; Aji, Muhammad Rendi Cahyono; Jihan, J (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Majlis Taklim is a non-formal religious educational institution that plays an important role in the spiritual and social development of the community. However, in Kunti Village, Andong District, Boyolali Regency, the management of the majlis taklim is still carried out traditionally, without a structured institutional management system. The Community Partnership Program (PKM) activity aims to empower and improve the capacity of the majlis taklim administrators through organizational management training, work program preparation, and institutional assistance. The method used is a participatory and educational approach, which actively involves the community in every stage of the activity. The results of the activity showed a significant increase in the ability of the majlis taklim administrators to manage programs and administration independently and professionally. The outputs of the activity include work program documents, an organized organizational structure, activity SOPs, and training modules. The evaluation showed a high level of satisfaction from participants, and there were indications of sustainability through the formation of local teams and support from external partners. This PKM makes a real contribution to strengthening community-based religious institutions and has the potential to be replicated in other areas.